Synthesis of Nanoflowers using Garcinia gummi-gutta Leaf Extract via Green Route for Enhanced Antifungal and Anti-cancerous Activities: Silver Nanoflowers with Biological Applications - Theresa Kurian, Jissa; Kadanthottu Sebastian, Joseph (Journal of Tropical Life Science, 2024)
Due to its envisaged relevance in nanomedicine and materials research, the bio-engineering of nanoparticles (NPs) is becoming progressively more promising. Compared to physical and chemical processes, green synthesis produces NPs that are less hazardous to the environment. The usage of phytochemicals in Garcinia gummi-gutta (L.) leaf extract (GGL) in the bio-reduction of GGL-Ag NPs with potential antifungal and anti-cancerous activities was the main focus of the current study. UV-vis spectrophotometry at 442 nm verified the synthesized GGL-Ag NPs. The average diameters of the synthesized GGL-Ag NPs were determined by scanning electron microscopy (SEM and zeta-sizer studies to be 166.69 nm and 148.2 nm, respectively. Energy dispersive X-ray spectroscopy (EDS) and X-ray diffraction (XRD) examinations of the GGL-Ag NPs confirmed the crystalline nature and the elemental constitution of the NPs. Additionally, the synthesized GGL-Ag NPs' FTIR spectra demonstrated the presence of Phyto components acting as capping agents. Zeta potential measurements (-26.2± 4.13 mV) authenticated the stability of the synthesized GGL-Ag NPs. Antimicrobial activity testing of the GGL-Ag NPs demonstrated considerable suppression against Candida tropicalis and Candida albicans at a dose of 100 µg/ml and 60 µg/ml. Additionally, the synthesized GGL-Ag NPs have demonstrated considerable cytotoxic effects on the Hep-G2 cell line. The current study results show that GGL- Ag NPs may be produced at a low cost and with minimal environmental impact for nanobiotechnology and biomedicine usage.